Most Influential Factors Affecting International Trade Flows: Bangladesh Context (Journal of Entrepreneurship and Business, 2022)
A country cannot go well without involving international trade because of the interconnected world economy. Every nation involves international trade for its economic welfare and some factors influence a lot to involve international trade. The influencing factors are factor endowments, trade policies, exchange rate, inflation rate, disposable income, and others. Bangladesh is doing well in international trade in recent years compared to eighty's decade, although the country is experiencing a negative trade balance regularly. The low-cost labour is an important influential factor that the country is using efficiently. National and intentional trade policies are influencing a lot of the international trade, for example, Venezuela, North Korea, Iran, and some other countries cannot involve in international trade expectedly due to the sanction of the USA. The economic diplomacy of Bangladesh is helping a lot but it could have improved. The inflation rate of Bangladesh was stable after 2012 which helps to maintain the international trade balance. Besides, the Exchange rate and foreign currency reserve are the motivational factors of international trade because domestic currency value is an important determinant of international trade. Bangladeshi BDT maintains an almost stable exchange rate with USD but after COVID-19 the rate fluctuated at a lower rate. To involve in international trade, there is no opportunity to avoid the influence of these factors or elements.Keywords: International Trade, factor endowments, trade policies, exchange rate, inflation rate, disposable income.
Keywords: Array; Array; Array; Array; Array; Array